2005
DOI: 10.1055/s-2005-861152
|View full text |Cite
|
Sign up to set email alerts
|

Gestörtes HörenDie apparative Versorgung der Schwerhörigkeit: Cochlea-Implantate und Hirnstammimplantate - Aktuelle Entwicklungen der letzten 10 Jahre

Abstract: Gestörtes Hören S 62 3.3.2 Chirurgische Aspekte der CI-Operation bei Kindern Bei der Indikationsstellung ist der individuelle Entwicklungsstand des Kindes zu bedenken: Zum Operationszeitpunkt sollte das Kind seine Kopfhaltung kontrollieren können, z. B. damit sich das Kind möglichst wenig den Kopf anstöût. So wird das Ri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…All of the children who were able to localize had been bilaterally implanted for a minimum of two years. In a similar study, Mueller (2005) showed that children implanted bilaterally for 18 months demonstrated localization to a sound source. Because the information reported here is drawn from clinical records, it is not possible to report the results of fixed time interval testing.…”
Section: Discussion and Summarymentioning
confidence: 87%
See 2 more Smart Citations
“…All of the children who were able to localize had been bilaterally implanted for a minimum of two years. In a similar study, Mueller (2005) showed that children implanted bilaterally for 18 months demonstrated localization to a sound source. Because the information reported here is drawn from clinical records, it is not possible to report the results of fixed time interval testing.…”
Section: Discussion and Summarymentioning
confidence: 87%
“…On the basis of parents' reports and clinical experiences, localization abilities typically become more precise over time (Mueller, 2005). Important factors in localizing environmental sounds and voices, especially in an uncontrolled acoustic environment are room acoustics and the characteristics of the sound produced.…”
Section: Localization Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Auf der anderen Seite werden durch Aufweitung der Indikationskriterien bei postlingualen ertaubten Patienten zunehmend hochgradig schwerh ö rige Patienten im Arbeitsprozess gehalten [8] .…”
Section: Olsa Bei Ci-patientenunclassified
“…Two years later, the Wuerzburg team performed the first bilateral implant in a child (Mueller, 1998(Mueller, , 1999. The success of these first two cases led to further investigations (Kuehn-Inacker, Shehata-Dieler, Mueller, & Helms, 2004) and influenced the acceptance of bilateral cochlear implants in children (Mueller, 2005).…”
Section: Introductionmentioning
confidence: 99%